Indicators of bee honey consumption in Lattakia Governorate - عليو محمود; غوش محمد (Latakia University Journal -Biological Sciences Series, 2021)
The research was carried out in Lattakia governorate on a random sample of 400 families distributed in all administrative regions of the governorate, including the countryside and the city, with the aim of knowing the quantitative and qualitative indicators related to the consumption of honey by the population in the governorate. The results of the research showed that bee honey is a popular product for most consumers, as the percentage of consumers who buy it reached (80%), with an annual average of (1.9) kg / family. It was also found that citrus honey was the most bought one in the sample by (90.31%) of the total consumers, with an annual average of (1.35) kg / family. And that the majority (60.63%) depend on the direct route (directly from the beekeeper). It was also observed that mountain honey is the most preferred among consumers (44.38%). Consumers’ tendencies to buy honey packaged in glass containers with a capacity of 1 kg are concentrated (56.25%). In terms of the appearance and morphological characteristics, it was found that the majority of consumers (46.88%) prefer dark honey over light honey, while in terms of texture, the majority of consumers (68.75%) prefer liquid honey over crystallized honey. As for consumption habits, it was found that (42.19%) of consumers consume honey at least once a week.